2000
DOI: 10.1093/geront/40.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Reality Orientation for Dementia

Abstract: The effectiveness of classroom reality orientation (RO) in dementia was evaluated by conducting a systematic literature review. This yielded 43 studies, of which 6 were randomized controlled trials meeting the inclusion criteria (containing 125 subjects.) Results were subjected to meta-analysis. Effects on cognition and behavior were significant in favor of treatment (cognition standardized mean difference [SMD] ϭ Ϫ 0.59; 95% confidence interval [CI] Ϫ 0.95-Ϫ 0.22; behavior SMD ϭ Ϫ 0.64, 95% CI ϭ Ϫ 1.20-Ϫ 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(42 citation statements)
references
References 19 publications
1
37
0
3
Order By: Relevance
“…Our group CST study 6 had an effect size of 0.32. Our Cochrane review of RO 26 found a standardised mean difference (SMD) of 0.58, whereas the individual RO/CST study 12 found a SMD of 0.41. Taking a conservative approach, we estimated the SMD relative to TAU to be 0.35.…”
Section: Exclusionmentioning
confidence: 85%
“…Our group CST study 6 had an effect size of 0.32. Our Cochrane review of RO 26 found a standardised mean difference (SMD) of 0.58, whereas the individual RO/CST study 12 found a SMD of 0.41. Taking a conservative approach, we estimated the SMD relative to TAU to be 0.35.…”
Section: Exclusionmentioning
confidence: 85%
“…A meta-analysis [29] on the efficacy of reality orientation in individuals suffering from dementia, which included 6 RCTs, concluded that this intervention has a positive effect on both cognitive and behavioural aspects. In the present review, we identified 9 reality orientation RCTs, including all those trials identified for the meta-analysis by Spector et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, we identified 9 reality orientation RCTs, including all those trials identified for the meta-analysis by Spector et al [29]. All trials described cognitive improvements (as measured by the MMSE or similar tests) independently of sample size, which varied from 15 resident patients in a home of elderly people [19] to 197 patients assisted in different centres [11].…”
Section: Discussionmentioning
confidence: 99%
“…L'analyse du comportement du patient apporte en général des indications quant aux mesures à mettre en oeuvre. Ces mesures dépendent donc directement du « savoir-faire » et du « savoir être » du personnel, mais aussi de l'environnement au sens plus large [92][93][94][95].…”
Section: Formationunclassified